Kebijakan Pemerintah Sumatera Utara dalam Mengatur Distribusi Pendapatan Sesuai Ekonomi Islam - Ulfa Rahmayani Assyfa Hasibuan; Ranah Santri Dongoran (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
In the Islamic economic system, income distribution is a very important aspect. The principles of Islamic economics emphasize justice and balance in the distribution of wealth and income in society. Government policy in regulating the distribution of income in accordance with the principles of Islamic economics aims to create a just, equitable and equitable society. If a nation has increased prosperity, but its distribution is not based on the true principles of justice it is not considered successful. Besides today's society has a lot of money. But on the contrary, many people around the community are still hurt by poverty. This shows that the unequal distribution of income and wealth distribution of goods is another form of economic activity that follows the production and consumption of products. The production results are then divided and transferred between parties. The method used in this distribution is identical to the exchange mechanism (mubilah), this mechanism is used to exchange production results for other production results or money. In Islamic law, this division of forms is mentioned in the context of aqad (transaction). The government plays an important role in how money is distributed throughout society. Because, as mentioned in the paragraph above, the poor who are afraid to beg have the right to their goods, as well as the poor who do not get their fair share. Islam recommends the distribution of wealth through zakat, alms, infaq, and other practices to maintain social peace.